Hydrologic and water quality performance of bioretention cells during plant senescence - Dhami, Jessica (2022)
Bioretention cells (also known as rain gardens) are a Low Impact Development (LID) method for sustainable stormwater management. An increasingly popular form of urban stormwater infrastructure, bioretention cells use an engineered, vegetated-soil-system to both reduce quantity and enhance quality of stormwater. The ability of bioretention systems to remove common pollutants from urban stormwater runoff, and reduce runoff volume through evapotranspiration, in a temperature climate during plant senescence were assessed in this full scale field-based study. Stormwater run-off simulations were conducted for 5-, 10-, and 25-year return period storm events at a field site in Victoria, British Columbia, Canada. Tests were run on both, a vegetated cell planted with a mix of Betula nigra, Betula nana, and Salix lutea, and a control cell with turfgrass. Influent and effluent field parameters were recorded for pH and dissolved oxygen (DO), in addition to lab analyses conducted to quantify COD, TN, TON, TP, ortho-phosphate, and TSS removal from the stormwater. Water quality and hydrologic performance were results were compared between the vegetated and control cell using a Wilcoxon Signed Rank Test. In addition, hydrologic results were correlated with daily Evapotranspiration (ET) and meteorological station data using Spearman’s Rho Correlation. The vegetated cells were more effective (p value < 0.05) at retention of water volume, DO, COD, and orthophosphate, when compared to the control. Strong correlations (p value < 0.05) were found between the retention of water volume, and each of ET, maximum temperature, average temperature, minimum temperature, and average wind, for only the vegetated cells. Graduate